Objective Neurophysiological Indices for the Assessment of Chronic Tinnitus Based on EEG Microstate Parameters - Yingying Wang; Peiying Zeng; Zhixiang Gu; Hongyu Liu; Shuqing Han; Xinran Liu; Xin Huang; Liyang Shao; Yuan Tao (IEEE, 2024)
Chronic tinnitus is highly prevalent but lacks precise diagnostic or effective therapeutic standards. Its onset and treatment mechanisms remain unclear, and there is a shortage of objective assessment methods. We aim to identify abnormal neural activity and reorganization in tinnitus patients and reveal potential neurophysiological markers for objectively evaluating tinnitus. By way of analyzing EEG microstates, comparing metrics under three resting states (OE, CE, and OECEm) between tinnitus sufferers and controls, and correlating them with tinnitus symptoms. This study reflected specific changes in the EEG microstates of tinnitus patients across multiple resting states, as well as inconsistent correlations with tinnitus symptoms. Microstate parameters were significantly different when patients were in OE and CE states. Specifically, the occurrence of Microstate A and the transition probabilities (TP) from other Microstates to A increased significantly, particularly in the CE state (32-37%, ${p}\le 0.05$ ); and both correlated positively with the tinnitus intensity. Nevertheless, under the OECEm state, increases were mainly observed in the duration, coverage, and occurrence of Microstate B (15-47%, ${p} < 0.05$ ), which negatively correlated with intensity ( $\text{R} < $ -0.513, ${p} < 0.05$ ). Additionally, TPx between Microstates C and D were significantly reduced and positively correlated with HDAS levels ( $\text{R}>$ 0.548, ${p} < 0.05$ ). Furthermore, parameters of Microstate D also correlated with THI grades ( $\text{R} < $ -0.576, ${p} < 0.05$ ). The findings of this study could offer compelling evidence for central neural reorganization associated with chronic tinnitus. EEG microstate parameters that correlate with tinnitus symptoms could serve as neurophysiological markers, contributing to future research on the objective assessment of tinnitus.